(untitled) (Società e diritti, 2023)
In her latest book, Cannibal Capitalism, Nancy Fraser precisely outlines the characteristics of neoliberalism. She represents it as the concluding form of capitalism and describes the Covid as the point where all the contradictions of capitalism converge. This paper intends to try to provide an answer to the question: when we speak of its “concluding form”, do we mean that capitalism has reached its terminal stage, or rather that it is preparing to take on a new guise?